2021
DOI: 10.3390/biomedicines9101463
|View full text |Cite
|
Sign up to set email alerts
|

GJA1 Expression and Left Atrial Remodeling in the Incidence of Atrial Fibrillation in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Obstructive sleep apnea syndrome (OSAS) is an important risk factor for atrial fibrillation (AF). GJA1 gene encoding connexin43, a major protein in cardiac gap junctions, plays a crucial role in the synchronized contraction of the heart and in cardiac arrhythmia. However, little is known regarding the role of GJA1 expression in the incidence of AF in patients with OSAS. All prospectively enrolled OSAS patients underwent polysomnography, electrocardiography, a 24-hour Holter test, and echocardiography. Moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…An overnight PSG study was performed on all individuals who were enrolled in this trial. The PSG procedures were described in detail in our previous research [30,31]. To summarize, the overnight PSG study was conducted in the sleep center of our hospital utilizing a commercial suite that has been standardized (Sandman Elite, Mallinckrodt Inc., St. Louis, MO, USA).…”
Section: Overnight Psg Study and Definition Of Srbd Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overnight PSG study was performed on all individuals who were enrolled in this trial. The PSG procedures were described in detail in our previous research [30,31]. To summarize, the overnight PSG study was conducted in the sleep center of our hospital utilizing a commercial suite that has been standardized (Sandman Elite, Mallinckrodt Inc., St. Louis, MO, USA).…”
Section: Overnight Psg Study and Definition Of Srbd Metricsmentioning
confidence: 99%
“…HL-1 cells are contractile and exhibit phenotypic characteristics similar to those of adult atrial cardiomyocytes [29]. Our previous study demonstrated that exosomes isolated from the plasma of OSAS patients with AF influenced GJA1 gene expression in HL-1 cells [30]. The purpose of this study was to determine the effect of exosomes from patients with and without significant OSAS on LA remodeling by analyzing the expression of genes in HL-1 cells treated with exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…35 Besides, in OSA patients there are several evidences of decreased atrial Cx43 expression and GJA1 expression, the gene encoding Cx43, which correlated with its severity independently of other concomitant diseases. [36][37][38] OSAWe, therefore, suggest that OSA patients may present a pro-arrhythmogenic state that favors the development of AF and this "environment" might remain in balance until a relevant factor, such as cardiac surgery, acts as the triggering "spark" leading to the development of de novo AF. Indeed, a study demonstrated in a rat model that cumulative exposure to sleep apnea-related conditions resulted in AF substrate and was associated with increased AF susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in mouse have reported that Cx40 deficiencies can lead to alterations in cardiac conduction and Cx40 expression was reduced in those 208−/− knockout mouse hearts 35 . Besides, in OSA patients there are several evidences of decreased atrial Cx43 expression and GJA1 expression, the gene encoding Cx43, which correlated with its severity independently of other concomitant diseases 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…70 Mutations in the genes of matrix metalloproteinases (MMP3), that maintain a balance between connective tissue synthesis and degradation, cartilage oligomeric matrix protein (COMP), that regulate ECM turnover, 71 and Collagen-encoding genes (COL12A1/COL23A1) that regulate fibrosis 72 and gap junction channels GJA5 (encoding Connexin40) 73 and GJA1 (encoding Cx43) also cause heart fibrosis and early AF. 4,74 Genes involved in cardiogenesis are also linked with risk of AF. Mutations in NKX2 DNA tracts, that are homebox-containing transcription factors involved in cardiac development and septation, 4 and GATA4 and GATA6 genes, that work synergistically with them, are associated with AF.…”
Section: Nucleotide Substitutionmentioning
confidence: 99%